2020
DOI: 10.1029/2019ja027290
|View full text |Cite
|
Sign up to set email alerts
|

MMS Observations of Intense Whistler Waves Within Earth's Supercritical Bow Shock: Source Mechanism and Impact on Shock Structure and Plasma Transport

Abstract: The properties of whistler waves near lower‐hybrid frequencies within Earth's quasi‐perpendicular bow shock are examined using data from the Magnetospheric Multiscale (MMS) mission. These waves appear as right‐hand polarized wave packets propagating upstream obliquely to the magnetic field and shock normal with phase speeds from a few hundred up to 1,600 km/s. The wavelengths are near the ion inertial length scale (λ∼  0.3–1.3 λi). Detailed analysis finds characteristics consistent with the modified two‐stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(79 citation statements)
references
References 56 publications
9
66
0
Order By: Relevance
“…Note that similar current densities have been found using multi-spacecraft techniques(Hull et al, 2020) supporting the results inWilson III et al (2014a) andWilson III et al (2014b).13 Note that Q o in this context is not the quasi-static terms in quasi-linear or linear theory but that from the DC-coupled measurements. Further, δQ is the fluctuating terms from these theories but the AC-coupled measurements, thus there is no a priori requirement that 〈δQ〉 0.14 https://www.cfa.harvard.edu/shocks/wi_data/.Frontiers in Astronomy and Space Sciences | www.frontiersin.org January 2021 | Volume 7 | Article 592634…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Note that similar current densities have been found using multi-spacecraft techniques(Hull et al, 2020) supporting the results inWilson III et al (2014a) andWilson III et al (2014b).13 Note that Q o in this context is not the quasi-static terms in quasi-linear or linear theory but that from the DC-coupled measurements. Further, δQ is the fluctuating terms from these theories but the AC-coupled measurements, thus there is no a priori requirement that 〈δQ〉 0.14 https://www.cfa.harvard.edu/shocks/wi_data/.Frontiers in Astronomy and Space Sciences | www.frontiersin.org January 2021 | Volume 7 | Article 592634…”
supporting
confidence: 74%
“…Prior to this study, the view by many in the community was that these fluctuating fields were completely negligible or just a minor, secondary effect. More recent, independent studies have performed similar analyses using different spacecraft and came to similar conclusions (Chen et al, 2018;Goodrich et al, 2018;Hull et al, 2020).…”
Section: Example Observations Versus Simulationsmentioning
confidence: 53%
“…The electron beams accelerated within the LW waves can be the source of the secondary instability to generate whistler waves. 41,42 The electron distributions observed in the SW modes also resemble electron distributions in modified two stream instabilities (MTSIs), 43,44 which can generate oblique whistler waves with frequencies near the lower hybrid frequency, 0.07 X e in the simulation with the mass ratio of 200, although the waves by MTSIs have been discussed in quasi-perpendicular shock waves. 45,46 As shown in Fig.…”
Section: Discussionmentioning
confidence: 84%
“…We note that Hull et al (2020) studied whistler generation at a shock with θ Bn = 82 • and M a = 10. They found that the reflected ion beam is in resonance with the waves, generating a whistler at frequency ∼ f lh through the kinetic cross-field streaming instability.…”
Section: Discussionmentioning
confidence: 99%
“…The magnetospheric multiscale (MMS) spacecraft (Burch et al, 2016) is a constellation of 4 spacecraft in a tetrahedral formation equipped with high-resolution field and particle instruments that allows the exploration of the microphysics of collisionless shocks in an unprecedented way. Hull et al (2020) used MMS data to conduct a case study about the generation mechanism and energetics of whistler waves upstream of quasi-perpendicular and super-critical shocks, with Alfvenic Mach number M a larger than the nonlinear whistler critical Mach number M cwn , so that no precursor whistlers are to be found and non-stationary behaviour of the shock is expected (Krasnoselskikh et al, 2002). They found that the kinetic cross field streaming instability of the reflected ions with the solar wind plasma is the likely source of the observed whistlers.…”
Section: Introductionmentioning
confidence: 99%